DESIGN AND DEVELOPMENT OF FEATURE ENGINEERING MODEL FOR CVD MULTI-DIMENSIONAL DATASETS STANDARDIZATION - Sangeetha V,; Syed Muzamil Basha, (Malaysian Journal of Computer Science, 2023)
Cardio Vascular Diseases (CVD) are most common medical abnormalities in modern times. According to World Health Organization (WHO), the CVD related deaths spot is higher and increased due to chronical reasons such as unhealthy lifestyle, food habits, geographical changes and comorbidities from genetic history. The studies are focused on one particular causes as it trends to eliminate the comorbidities influencing the secondary causes. Hence a large unbalanced prediction and independent datasets are created and customized. In this research, the authors have aimed to propose dataset standardization on CVD. The proposed standardization is based on attribute interdependency mapping and indexing. The attribute interdependency from one influencing parameter is aligned and coordinated with secondary attributes from relationship/dependency evaluation. Further, the dependency mapping is simplified by layering and customizing the data attributes. The multi-dimensional CVD datasets extracted in this process is mapped and tracked from feature engineering process. The dataset standardization of CVD is novel and first of its kind in data analytics and processing.